Active emigration from climate change-caused seawater intrusion into freshwater habitats. (March 2020) - Venâncio, C.; Ribeiro, R.; Lopes, I.
Abstract: Ecological risk assessment associated with seawater intrusions has been supported on the determination of lethal/sublethal effects following standard protocols that force exposure neglecting the ability of mobile organisms to spatially avoid salinized environments. Thus, this work aimed at assessing active emigration from climate change-caused seawater intrusion into freshwater habitats. To specific objectives were delineated: first, to compute median 12-h avoidance conductivities (AC50, 12h ) for freshwater species, and second, to compare it with literature data (LC50, 48 or 96h, EC50, 6 or 21d ) to assess the relevance of the inclusion of stressor-driven emigration into risk assessment frameworks. Four standard test species, representing a broad range of ecological niches – Daphnia magna, Heterocypris incongruens, Danio rerio and Xenopus laevis – were selected. The salt NaCl was used as a surrogate of natural seawater to create the saline gradient, which was established in a 7-compartment system. At each specific LC50, 48 or 96h, the proportion of avoiders were well above 50%, ranging from 71 to 94%. At each LC50, considering also avoiders, populations would decline by 85–97%. Furthermore, for D. magna and X. laevis it was noticed that at the lowest conductivities eliciting mortality, the avoidance already exceeded 50%. The results showed that the emigration from salinity-disturbed habitats exists and that can even be more sensitive than standard endpoints. Looking solely to standard endpoints involving forced exposure may greatly underestimate the risk of local population extinction, because habitat function can be severely disrupted, with subsequent stressor-driven emigration, before any adverse physiological effects at the organism level. Thus, the present study highlights the need to include non-forced exposure testing into ecological risk assessment, namely of salinity-menaced costal freshwaters. Graphical abstract: Image 1 Highlights: Freshwater ostracods, cladocerans, tadpoles, and fish larvae spatially avoided salinity. Median avoidance conductivities (AC50, 12h ) were 64–76% the standard LC50, 48 or 96h . At each LC50, considering also avoiders, populations would decline by 85–97%. Standard tests underestimate ecological risk of seawater intrusion into freshwaters. Abstract : Salinity-driven emigration of considerable proportions of the populations may compromise freshwater habitat function.